2022
DOI: 10.3390/molecules27196712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Odorants in Beef and Chicken Broth—Focus on Thiazoles and Thiazolines

Abstract: The shift in consumer landscape towards vegan, vegetarian and flexitarian diets has created an unprecedented challenge in creating meat aroma from plant-based alternatives. The search for potential vegan solutions has thus led to a renewed interest in authentic meat flavour profiles. To gain a better understanding of the qualitative odour differences between boiled beef and boiled chicken, aroma extracts were isolated using Likens-Nickerson simultaneous distillation-extraction (SDE), selected expressly because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…2-ethyl furan has a burnt aroma, pentanoic acid has a sweaty aroma, and propanoic acid has a pungent aroma. 2-Propanethiol-D has a raw onion aroma, and sulfur compounds are often considered key compounds despite their relatively low levels in foods ( Yeo, Balagiannis, Koek, & Parker, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-ethyl furan has a burnt aroma, pentanoic acid has a sweaty aroma, and propanoic acid has a pungent aroma. 2-Propanethiol-D has a raw onion aroma, and sulfur compounds are often considered key compounds despite their relatively low levels in foods ( Yeo, Balagiannis, Koek, & Parker, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“… No. Compounds Odor threshold Value (mg/kg) Relative content (%) ROAV Flavor description References CO EX CO EX 1 (E)-hept-2 enal 0.0005 2.50 3.00 100 100 green, leaf, fat ( Li et al, 2023 , Li et al, 2023 , Li et al, 2023 ) 2 2-propanethiol-D 0.00005 0.20 0.22 78.08 73.26 raw onion ( Yeo et al, 2022 ) 3 2-methylpropanal-M 0.0007 0.25 0.39 7.27 9.19 malty ( Grimm & Steinhaus, 2019 ) 4 2-methyl-2-propenal 0.015 5.13 4.84 6.83 5.37 5 tert -butylmethylether-D 0.015 4.29 4.78 5.70 5.30 minty ( Sun, Chen, Xiang, Hu, & Zhao, 2022 ) 6 ethyl propanoate 0.0049 1.34 1.11 5.45 3.78 nail polish-like ( Sun et al, 2018 ) 7 ethyl acrylate 0.018 …”
Section: Resultsmentioning
confidence: 99%
“…Esters in meat products are formed by the esterification of carboxylic acids and alcohols and have a relatively low odor threshold [68]. Generally, esters of short-chain fatty acids provide fruit and sweet taste, while esters of long-chain fatty acids produce a fatty smell [69]. We screened different volatile flavor compounds based on VIP score in OPLS-DA and found that the 2-hexene-1-ol acetate monomer had the largest VIP value.…”
Section: Effect Of Different Processing Methods On the Flavor Of Bts ...mentioning
confidence: 99%